Power Sharing Between Peace and Conflict Times: A Case Study of LIBERIA - Taha Shabbir (Universitas Negeri Makassar, 2021)
Power-sharing is an effective way to end the conflict, but an ineffective way to build peace. What impact do power-sharing institutions established as part of civil war settlements have on the establishment of the rule of law in post-civil war states? We argue that power-sharing policies aid the development of the rule of law in two ways. For starters, they provide a kind of institutional restriction that supports judicial authority and independence. Second, they instill a feeling of security among judges and other political actors, which strengthens their commitment to the rule of law. Through an examination of post–civil war nations between 1948 and 2006, we show the possibility of a positive connection between power sharing and the rule of law. Our results indicate that civil war settlements may aid in the establishment of the rule of law if they contain measures targeted at assuaging political players' fears in the post conflict environment. Contrary to popular belief, it may even harm the peace effort. For certain instances, the regional level is over-emphasized, while for others, it is romanticized. Regardless, centralized policies, the development of centralized balances of power, and the history of spatial-political connections all help contribute to a centralized system. This recognition of local monopolies of power (as opposed to local balance, which occurs when power is divided between several factions) may alleviate a security problem for rebel groups, persuading them to lay down their weapons. We differentiate two types of local power-sharing in the rest of this article: local balances of power and the juxtaposition of local monopolies of power.